Patients’ online access to their electronic health records and linked online services: a systematic review in primary care - Mold, F; de Lusignan, S; Sheikh, A; Majeed, A; Wyatt, JC; Quinn, T; Cavill, M; Franco, C; Chauhan, U; Blakey, H; Kataria, N; Arvanitis, TN; et al. (Royal College of General Practitioners, 2015)
Background Online access to medical records by patients can potentially enhance provision of patient-centred care and improve satisfaction. However, online access and services may also prove to be an additional burden for the healthcare provider.